THE ANTIBACTERIAL EFFECT OF ROSELLE (Hibiscus sabdariffa) EXTRACT AGAINST Staphylococcus epidermidis IN VITRO - Lusida, Terrence Timothy Evan; Hermanto, Bambang; Sudarno, Sudarno (Institute of Topical Disease Universitas Airlangga, 2017)
Infection of Staphylococcus epidermidis is still a common problem in many hospitals. Factor determining biofilm formation makes it harder for atibiotics to cure the infection. Roselle (Hibiscus sabdariffa), a well known traditional medicine plant, is a potential candidate as a drug againts infectious disease. The purpose of this research is to investigate the antibacterial effect of ethanol extract from Roselle (Hibiscus sabdariffa) calyx againts the growth of Staphylococcus epidermidis. Assessment for antibacterial effect is performed using broth diffusion method. The extract is made by maceration of the calyx of Roselle in 96% ethanol. Extracts with concentration of 125, 62.5, 31.25, 15.63, 7.81, 3.90, 1.95, 0.97, 0.48, 0.24 mg/mL are added into separated Mueller-Hinton broths (MHB), which have already been inoculated by Staphylococcus epidermidis. As for bacterial growth control, we used MHB with bacterial inoculation, while sterility control we used mixture of extract and MHB. Then from each broth, the solutions are added into separated nutrition agar plates. Replications are done three times. Clarity and bacterial growth are observed after 24 hours of incubation. However, clarity cannot be observed in 36 broth, but bacterial growth is observed on the plate for concentration 0.97, 0.48, and 0.24 mg/mL. Therefore Minimum inhibitory concentration (MIC) cannot be determined because the extract's color interfere the observation. While minimum bactericidal concentration (MBC), the last concentration before the concentration where the bacteria are still viable, is 1.95 mg/mL. Based on the result of the research, the Roselle calyx ethanol extract (Hibiscus sabdariffa) through dilution method with a concentration of 1.95 mg / mL can kill Staphylococcus epidermidis and in order to find MIC in collored and turbid solution (before being incubated in incubator), we can consider using agar dilution methode or microdilution methode.